Potensi Keefektifan Harapan Ensiklopedia Genus Bulbophyllum Berbasis Potensi Lokal KHDTK Tahura Sultan Adam Mandiangin dalam Melatih Keterampilan Berpikir Kritis Mahasiswa: (Potential Expected Effectiveness of a Bulbophyllum Genus Encyclopedia Based on Local Potential of KHDTK Sultan Adam Mandiangin Tahura in Developing Students’ Critical Thinking Skills) - Khasanah, Khayatun; Zaini , Muhammad (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Critical thinking skills are a crucial competency to be developed within the context of 21st-century higher education. However, there is still a need to enhance students' critical thinking skills through the use of contextual teaching materials that support the learning process. This study aimed to examine the potential effectiveness of a *Bulbophyllum* genus encyclopedia—based on the local biodiversity of the Sultan Adam Grand Forest Park (Tahura Sultan Adam)—in fostering students' critical thinking skills. The study employed an Educational Design Research (EDR) approach utilizing Tessmer’s formative evaluation model, specifically focusing on the small-group evaluation stage. The participants consisted of four students from the Biology Education Study Program who had previously completed the Phanerogamae course. Data regarding potential effectiveness were gathered through Student Worksheets (LKM)—designed to cultivate critical thinking skills—and an instrument assessing students' metacognitive skills. The data were analyzed using descriptive quantitative methods based on obtained scores to determine the category of potential effectiveness. The results indicated that the *Bulbophyllum* genus encyclopedia achieved a